The history and current epidemiology of malaria in Kalimantan, Indonesia - Sri Riyati, Sugiarto; J. Kevin, Baird; Balbir, Singh; Iqbal, Elyazar; Timothy M.E., Davis (BioMed Central Ltd, 2022)
Kalimantan is a part of Indonesia, which occupies the southern three-quarters of the island of Borneo, sharing a border with the Malaysian states of Sabah and Sarawak. Although most areas of Kalimantan have low and stable transmission of Plasmodium falciparum and Plasmodium vivax, there are relatively high case numbers in the province of East Kalimantan. Two aspects of malaria endemicity in Kalimantan diferentiate it from the rest of Indonesia, namely recent deforestation and potential exposure to the zoonotic malaria caused by Plasmodium knowlesi that occurs in relatively large numbers in adjacent Malaysian Borneo. In the present review, the history of malaria and its current epidemiology in Kalimantan are examined, including control and eradication eforts over the past two centuries, mosquito vector prevalence, anti-malarial use and parasite resistance, and the available data from case reports of knowlesi malaria and the presence of conditions which would support transmission of this zoonotic infection.